Scale, evidence, and community participation matter: lessons in effective and legitimate adaptive governance from decision making for Menindee Lakes in Australia’s Murray-Darling Basin - Zoe E. Ford; Sue Jackson; Gilad Bino; Kate J. Brandis; Richard T. Kingsford (Ecology and Society, 2023)
Rivers and their interdependent human communities form social-ecologically complex systems that reflect basin scale functionally but are often governed by spatially mismatched governance systems. Accounting for this complexity requires flexible adaptive governance systems supported by legitimacy in decision-making processes. Meaningful community dialogue, information exchange, transparency, and scientific rigor are essential to this process. We examined failings in the adaptive governance of the Menindee Lakes system, a major Australian wetland system on the Barka/Darling River of the Murray-Darling Basin. Ecological sustainability of the Menindee Lakes was a casualty of a top-down governance, driven by the New South Wales Government in pursuit of “water savings” for the Murray-Darling Basin, a large scale, federally influenced region. We used quantitative and qualitative methods to analyze long-term social-ecological impacts and stakeholder perceptions of adaptive governance. State and federal government agencies failed basic processes of adaptive governance, ignoring local environmental sustainability in pursuit of basin scale objectives at great cost to governments, communities, humans, and non-humans. This resulted in the development of an ineffective, technocratic solution that lacked community input, leading to a complete loss of support by local communities, including traditional owners. We emphasize the importance of elements of scale in adaptive governance projects, if such projects are going to be effective and legitimate with consequences of coarse commitments to large spatial scale political and environmental objectives.